2013
DOI: 10.1155/2013/793505
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Phospholipases A2in Asthma and Chronic Obstructive Pulmonary Disease

Abstract: The increased morbidity, mortality, and ineffective treatment associated with the pathogenesis of chronic inflammatory diseases such as asthma and chronic obstructive pulmonary disease (COPD) have generated much research interest. The key role is played by phospholipases from the A2 superfamily: enzymes which are involved in inflammation through participation in pro- and anti-inflammatory mediators production and have an impact on many immunocompetent cells. The 30 members of the A2 superfamily are divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 105 publications
1
25
0
4
Order By: Relevance
“…Childhood asthma represents a significant burden, not only in terms of morbidity and reduced quality of life but also in terms of healthcare costs, as reflected by the high rates of unscheduled emergency department visits, hospitalization, and school absenteeism [5]. In developing countries, the terms “chest allergy” and “dyspnea” are commonly used instead of asthma to avoid the social stigma associated with the chronic nature of the disease [6].…”
Section: Introductionmentioning
confidence: 99%
“…Childhood asthma represents a significant burden, not only in terms of morbidity and reduced quality of life but also in terms of healthcare costs, as reflected by the high rates of unscheduled emergency department visits, hospitalization, and school absenteeism [5]. In developing countries, the terms “chest allergy” and “dyspnea” are commonly used instead of asthma to avoid the social stigma associated with the chronic nature of the disease [6].…”
Section: Introductionmentioning
confidence: 99%
“…The PLA 2 family includes six main types: cytosolic (cPLA 2 ), secreted (sPLA 2 ), calcium-independent (iPLA 2 ), platelet-activating factor acetylhydrolase (PAF-AH) also referred to as lipoprotein-associated phospholipase A 2 (Lp-PLA2), lysosomal phospholipase A 2 (L-PLA2), and adipose-PLA 2 (AdPLA) [1]. During the last decade, it has been shown that PLA 2 s are associated with several inflammatory diseases including asthma, arthritis, and cancer, and thus constitute an attractive target for inhibitor development [6-8]. …”
Section: Introductionmentioning
confidence: 99%
“…AA and other PUFAs are metabolic precursors for the biosynthesis of eicosanoids, including prostaglandins and leukotrienes, which are implicated in many inflammatory conditions (2). Through the eicosanoid pathways, PLA 2 s have been implicated in many inflammatory diseases, including asthma, arthritis, atherosclerosis, pain, and cancer (3)(4)(5). There are 16 groups and many subgroups of PLA 2 , but they can be considered as six types: cytosolic (cPLA 2 ), secreted (sPLA 2 ), calcium-independent (iPLA 2 ), platelet-activating factor acetylhydrolase (PAF-AH), also known as lipoproteinassociated PLA 2 (Lp-PLA 2 ), lysosomal PLA 2 (LPLA 2 ), and adipose-PLA 2 (AdPLA 2 ) (1).…”
mentioning
confidence: 99%